Intensive care unit nurses’ perceptions of the necessity for ICU outreach services in Malaysia - Mohamed Ludin, Salizar (IIUM Press, 2018)
Objective: International studies show that ICU outreach services help to improve patients' condition and reduce both the length of hospital stays and mortality rates. However, Malaysian nurses’ perceptions of ICU outreach services and their implementation have previously remained uninvestigated. This study thus aims to uncover Malaysian nurses’ perceptions of implementing Intensive Care Unit (ICU) outreach services. Method: An exploratory mixed method was used, focusing on 47 Malaysian hospital ICU nurses, using surveys and interviews over a 2-month period in 2015. All those who met the inclusion criteria were purposively recruited into the study. Results: A total of 47 respondents completed the questionnaires. The mean years of employment was 9.72 and mean age was 33.6 years. Only seven respondents had undertaken an intensive care course and had knowledge of ICU outreach services. Years of employment and highest education level were not significantly related to awareness of ICU outreach services. Major themes emerging from the interviews included ICU outreach service benefits, ICU readmission events, and nurses’ readiness for ICU outreach services. Interview data supported the survey results consistently. Conclusion: Nurses are aware of the advantages of ICU outreach services for both nurses and patients, despite the fact that there is no official implementation of such services in Malaysia. Their appreciation of the importance of ICU outreach services, and enthusiasm to participate in a new program to improve ICU survivors’ condition and care in general wards, indicates the potential for better care in the future.